Is that lift diagram correct? A visual study of flight education literature. (15th March 2023) - Wild, Graham
Abstract: With a complex topic such as aerodynamics, subtle points are critical. In this work images illustrating air flow around wings and aerofoils were studied to explore misunderstandings in aerodynamics education. While these images are common in textbooks and popular science media, this study was limited to the 135 physics education articles on the topic of lift, of which 49 contained illustrations of air flow around an aerofoil or wing. These 49 cases were included for qualitative comparison using visual semiotics. It was found that 28% of images did not include upwash, and only 44% included stagnation points. For the case of 2D flow around aerofoils 30% were illustrated correctly, while for wings 75% were correct. These results excluded the seven completely incorrect illustrations where common misconceptions were presented as facts. Most illustrations of flow around an aerofoil incorrectly depicted flow around a wing.